Wireless data acquisition for assistance with mobile application in the sizing of a photovoltaic system in the province of Chepen - Chavez-Gallegos, Eduardo; Trauco-Mas, Ronal; Gutierrez-Tirado, Ricardo; Chavez-Sanchez, Wilmer; Mendoza-Nolorbe, Juan; Gamarra-Suchero, Martin (LACCEI, 2024)
Currently, the use of photovoltaic systems as a source of energy has increased. However, its installation requires hiring specialized professionals to perform complex calculations for the sizing of photovoltaic systems. The objective of this research is to develop a mobile application that receives and analyzes different physical parameters to size the photovoltaic system in different districts of the city of Chepén. For this reason, portable bases were developed to detect irradiation and geolocation, which were placed within the districts of Chepén and wirelessly sent the data through Firebase to a mobile application that performed the sizing calculations. The result was obtained when comparing the districts of Chepén and Pacanga that the district with better radiation and that required the use of fewer solar panels was Chepén. It is concluded that a larger area can be analyzed using the portable bases to identify the location with the most convenient sizing and that the application can help people who are not related to the field of photovoltaic energy.